Accelerated aging and controlled deterioration of peanut seeds - Rossetto, Claudia Antonia Vieira; Lima, Tatiana de Moraes; Guimarães, Eduardo da Costa (Pesquisa Agropecuaria Brasileira, 2004)
Researches have been developed aiming to determine the procedures for physiological potential seeds evaluation with emphasis to vigour tests. The objective was to study the controlled deterioration and the accelerated aging in peanut (Arachis hypogaea) seeds vigour. Four lots of peanut seeds were submitted to the ageing accelerated test, at 42°C or 43°C, for 48 hours and 72 hours, with or without the use of saturated solution of NaCl, and controlled deterioration test, with 15% and 20% water content, at 40°C or 45°C, for 48 hours. The evaluation of water content, germination and health test was accomplished. There was no different performance among the four lots by the germination and emergency tests. In the ageing accelerated test with saturated solution, the period of 72 hours at 42°C introduces sensibility to evaluate seeds physiological potential. In the controlled deterioration test, the combination of 15% of water content, for 48 hours at 45ºC, is efficient to detect vigor differences among peanut seed lots.